PO188 Hereditary spastic paraplegia, epilepsy and motor neurone disease in a family with nipa1 mutation. (1st December 2017) - Tanti, Matthew; Mirza, Nasir; Young, Carolyn
Abstract : The hereditary spastic paraplegias (HSP) are a diverse group of conditions affecting the corticospinal tracts. Rarely HSP has been associated with other neurological diseases. NIPA1 mutations are usually associated with pure HSP and rarely implicated in HSP with epilepsy. There exists one report of a patient with HSP, MND and NIPA1 mutation. We present the first report of a patient with HSP, epilepsy, MND and family history, associated with NIPA1 mutation. Our patient presented in her 30's with progressive leg stiffness and urinary frequency. Her sister, father and paternal grandfather had a diagnosis of HSP; after normal investigations she was diagnosed with HSP. She had childhood fits but at age 38 blank spells recurred and electroencephalography confirmed idiopathic generalised epilepsy. Two decades after HSP diagnosis she developed bulbar symptoms, breathing difficulty and limb weakness. Electromyography was consistent with MND. Her father had HSP and also developed MND in later life. Genetic testing in the index patient revealed a heterozygous NIPA1 mutation [c.316 G>A, p. (Gly106Arg) in exon 3]. A niece with epilepsy and HSP also has a NIPA1 mutation. This case adds to recent evidence suggesting an association between NIPA1 and MND and highlights the complexity of HSP.